Uplift Dynamics of the Obducted Northeastern Continental Margin of the Arabian Peninsula, Sultanate of Oman - Pavlopoulos, Kosmas (2023)
Eustatic sea level changes and vertical tectonic movements are producing uplifted paleoshorelines. Along subduction zones, uplifted terraces are used to study fault activities and, overall, allow to interpret the tectonic history of plate convergence. Northeastern Oman is experiencing plate convergence following the late Cretaceous obduction of the Semail Ophiolite. Post‐obduction shallow‐marine carbonates have been uplifted to different elevations from 133 to >2,000 m. The present study employs a multidisciplinary approach to elucidate the variability in relief and to introduce a geodynamic model that extends beyond the temporal constraints imposed by the late Quaternary age of the sediments found on the uplifted terraces. Stratigraphic and fault analyses produced a post‐obductional geodynamic model to advance the existing regional models in the framework of the subduction of the Arabian Plate in the Makran Zone. In addition, we rely on imaging geodesy, geomorphology and dating to explain the late Quaternary uplift scenario. Overall, analyses of geomorphology, stratigraphy, and fault patterns reveal spatially heterogeneous post‐late Cretaceous uplift in the region. Compartmentalization by major faults created individual blocks and relief variability. Within the timeframe of marine terrace formation (late Quaternary), we also observed spatially varied displacements. Ground displacements by Interferometric Synthetic Aperture Radar document an ongoing spatial heterogenous uplift at approximately 1.3 mm/a. Finally, temporal variability was evident during the late Quaternary by unusually high late Pleistocene (<40 ka) uplift rates averaging ≥2 mm/a in younger terraces, while for older terraces (>40 ka) the uplift rate is distinctly lower (<1 mm/a)